A study on the frontal oblique collision-induced derailment mechanism in subway vehicles. (July 2020) - Yao, Shuguang; Zhu, Huifen; Liu, Mingyang; Li, Zhixiang; Xu, Ping; Che, Quanwei
Oblique collisions can more easily lead to train derailment and cause heavy casualties. In this paper, a fine finite-element model of a subway head vehicle–rigid wall frontal oblique collision was established and validated by a single wheelset derailment simulation. Furthermore, the derailment mechanisms and patterns under an oblique impact angle of 6.34°–40° and at an impact speed of 8–40 km/h were studied via simulation. The results indicated that three types of derailment, such as roll-over derailment, climb/roll-over derailment and wheel-lift derailment, have occurred. When the impact speed was set to 25 km/h, a climb/roll-over derailment occurred under the impact angle of greater than 40°; a roll-over derailment occurred under the impact angle of 20°–40°; and the vehicle would not derail when the impact angle was less than 15°. When the impact angle was 6.34°, the vehicle was in danger of wheel-lift derailment with the largest wheel vertical displacement of 26.83 mm and lateral displacement of 12.52 mm under the impact speed of 40 km/h, but it was safe with the largest displacement of no more than 18 mm and lateral displacement of 8.39 mm if the impact speed was less than 40 km/h. It is shown that the derailment patterns are more sensitive to the impact angle. Therefore, both the lateral and vertical displacements should be considered when studying the oblique collision-induced derailment mechanisms and patterns.